Requirements for adopting supply chain management in the Health Secto (A survey study on Private Hospitals in Lattakia Governorate) (Journal of Hama University, 2021)
This study aimed to clarify the requirements for adopting a supply chain management (relationship with suppliers, relationship with brokers and distributors, relationship with customers) in special hospitals in Lattakia governorate.The researcher followed the descriptive approach in her study, and a set of methods, including relying on secondary and primary data, through a questionnaire that was designed by familiarizing the researcher with the published literature, and it was distributed to (174) respondents, from which (170) were retrieved, and (165) questionnaires were suitable for analysis. The research community consisted of a cadre of employees and customers in the special hospitals departments in Lattakia governorate (hospital manager, department heads, employees, orderlies, and patients), and then the SPSS program was relied upon as a tool for analyzing the available data in order to characterize each of the study axes.The results of the study found the continuity of the relationship between suppliers and private hospitals and the failure of private hospitals to establish long-term personal relationships with customers, and joint solution to problems existing between hospitals, mediators and distributors and solving complaints from customers.